Symposium on market development and inequality in China - Kanbur, Ravi; Qian, Yingyi; Zhang, Xiaobo (Wiley, 2008)
After three decades of market development, the problem in China is no longer how to achieve growth but how to manage its consequences and how to sustain it. One of the most important consequences is the growing inequality – between skilled and unskilled workers, between the genders, between rural and urban areas, and between inland and coastal regions. The papers in this symposium shed light on the important issue of inequality during rapid market development in China. Analysis based on ground level empirical studies can help us to understand better the sources of the rising inequality and to illuminate the nature of the future challenges.